2012
DOI: 10.1002/jrs.4159
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopy of carbon‐based black pigments

Abstract: Carbon-based black pigments are a wide group of dark-colored materials, which are classified according to the starting material used and their method of manufacture. Raman spectroscopy is an ideal technique for the characterization of carbonaceous matter: crystalline carbon materials present well-defined peaks, which can be easily assigned; amorphous carbon materials, on the other hand, show broad bands between 1300 and 1600 cm À1 . The aim of this work was the discrimination between carbon-based pigments by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 26 publications
3
101
0
3
Order By: Relevance
“…I Defects [43,52,54] ; soot features, [33,51,56] like mixed sp 2 -sp 3 bonds or polyenic structures [45,47,58] ; char and coal tar [48] ; diamondlike carbon in anthracite [71] ; sp 3 carbons [59,72] ; nanocrystalline diamond or trans polyene ν 1 [57] ; defects related to oxygen rich precursors as wood [60,61] From 1050 with deep UV excitation [57] to 1127 [51] to 1275 [48] [23,33,45,47,[52][53][54][55][56][57][58][59][60][61]71,72] Fullerenes Phototransformation/oxidation [38,73] 1459-1469 and 930-970 [38,73] Rhombohedral graphite B 2 2g [48] 1400 [48] ; [49] 1800 1400 1200 1000 800 1600…”
Section: D4mentioning
confidence: 99%
See 1 more Smart Citation
“…I Defects [43,52,54] ; soot features, [33,51,56] like mixed sp 2 -sp 3 bonds or polyenic structures [45,47,58] ; char and coal tar [48] ; diamondlike carbon in anthracite [71] ; sp 3 carbons [59,72] ; nanocrystalline diamond or trans polyene ν 1 [57] ; defects related to oxygen rich precursors as wood [60,61] From 1050 with deep UV excitation [57] to 1127 [51] to 1275 [48] [23,33,45,47,[52][53][54][55][56][57][58][59][60][61]71,72] Fullerenes Phototransformation/oxidation [38,73] 1459-1469 and 930-970 [38,73] Rhombohedral graphite B 2 2g [48] 1400 [48] ; [49] 1800 1400 1200 1000 800 1600…”
Section: D4mentioning
confidence: 99%
“…[8,20] The continuity of use through time and the worldwide distribution of this kind of materials require the establishment of a welldefined terminology that could be easily used for archaeometrical applications, but that keeps into account the major contributions of geological and industrial research to the study of carbon-based materials, along with the information from artistic literature (treatises [1,21,22] ). The lack of archaeometrical literature on the specific topic of distinguishing among different carbon-based black pigments [3,23] made necessary a survey of geological and industrial literature, which indeed suggested some useful ideas for data processing and interpretation, while many aspects were not considered. This latter fact is mainly because of an important consideration, which is the non-correspondence between geological and artistic nomenclature.…”
Section: Introductionmentioning
confidence: 99%
“…5), which are characteristic of the D and G bands of amorphous carbon (Tomasini et al 2012;Lahlil et al 2012). The absence of bands close to 960 cm −1 , which are characteristic of phosphates present in bony elements, leads us to dismiss the hypothesis that these elements were the raw material of the pigment (Tomasini et al 2012, Gomes et al 2013, Lahlil et al 2012.…”
Section: Resultsmentioning
confidence: 95%
“…Para el caso de las muestras negras, el análisis espectral identifica claramente el uso de carbón amorfo como base de la composición pictórica, lo que es evidente por la presencia de las bandas cercanas a 1335 y 1590 cm -1 , correspondiente a las bandas D y G de carbón amorfo ( fig. 6) (Lahlil et al 2012;Tomasini et al 2012b). Un análisis más acabado del perfil espectral nos permite inferir que el carbón amorfo identificado no tiene como fuente de origen restos óseos, debido a la ausencia de la banda característica cercana a 970 cm -1 (Lahlil et al 2012;Tomasini et al 2012b;Gomes et al 2013).…”
Section: Resultsunclassified
“…6) (Lahlil et al 2012;Tomasini et al 2012b). Un análisis más acabado del perfil espectral nos permite inferir que el carbón amorfo identificado no tiene como fuente de origen restos óseos, debido a la ausencia de la banda característica cercana a 970 cm -1 (Lahlil et al 2012;Tomasini et al 2012b;Gomes et al 2013). Además, en ningún caso fue posible identificar otros componentes presentes en esta capa pictórica, como por ejemplo, aglutinantes o cargas.…”
Section: Resultsunclassified